Expression of sall4 in taste buds of zebrafish. Issue 7 (14th May 2013) - Jackson, Robyn; Braubach, Oliver R.; Bilkey, Jessica; Zhang, Jing; Akimenko, Marie‐Andrée; Fine, Alan; Croll, Roger P.; Jonz, Michael G.
ABSTRACT We characterized the expression of sall4, a gene encoding a zinc finger transcription factor involved in the maintenance of embryonic stem cells, in taste buds of zebrafish (Danio rerio). Using an enhancer trap line (ET5), we detected enhanced green fluorescent protein (EGFP) in developing and adult transgenic zebrafish in regions containing taste buds: the lips, branchial arches, and the nasal and maxillary barbels. Localization of EGFP to taste cells of the branchial arches and lips was confirmed by co‐immunolabeling with antibodies against calretinin and serotonin, and a zebrafish‐derived neuronal marker (zn‐12). Transgenic insertion of the ET construct into the zebrafish genome was evaluated and mapped to chromosome 23 in proximity (i.e. 23 kb) to the sall4 gene. In situ hybridization and expression analysis between 24 and 96 h post‐fertilization (hpf) demonstrated that transgenic egfp expression in ET5 zebrafish was correlated with the spatial and temporal pattern of expression of sall4 in the wild‐type. Expression was first observed in the central nervous system and branchial arches at 24 hpf. At 48 hpf, sall4 and egfp expression was observed in taste bud primordia surrounding the mouth and branchial arches. At 72 and 96 hpf, expression was detected in the upper and lower lips and branchial arches. Double fluorescence in situ hybridization at 3 and 10 dpf confirmed colocalization of sall4 and egfp in the lips and branchial arches. These studies reveal sall4 expression in chemosensory cells and implicate this transcription factor in the development and renewal of taste epithelia in zebrafish. © 2013 Wiley Periodicals, Inc. Develop Neurobiol 73: 543–558, 2013